Peran Strategi Bisnis dalam Meningkatkan Revenue: (Studi Kasus Pedagang Bakso Kojek di Kota Medan) - Cindy Amellia Putri; Aurick Mathias Danarya Purba; Luna Maya Sitepu; Novita Yanti Sari Aritonang; Dionisius Sihombing; Fadli Agus Triansyah (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to analyze the role of business strategies in increasing revenue for micro, small, and medium enterprises (MSMEs), using the case study of Bakso Kojek vendors in Medan City. The background of the research is based on the increasingly intense competition in the culinary business, which requires effective business strategies to maintain existence while driving revenue growth. The research method used is a qualitative approach with data collection techniques through direct observation, semi-structured interviews, and documentation. The results of the study show that the business strategies implemented by Bakso Kojek vendors include consistently maintaining product quality, providing friendly service, selecting strategic business locations, and creative promotion through social media. These strategies have proven effective in attracting new customers, retaining existing customers, and sustainably increasing revenue. It can be concluded that the success of Bakso Kojek vendors in Medan City is largely attributed to their ability to adapt to market demands and competition by implementing strategic business decisions. The study suggests that other MSMEs in similar industries may benefit from adopting these strategies to enhance their revenue growth and business sustainability.